2021
DOI: 10.4252/wjsc.v13.i10.1382
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the morphogenetic code: A new path at the intersection of physical energies and chemical signaling

Abstract: In this editorial, we discuss the remarkable role of physical energies in the control of cell signaling networks and in the specification of the architectural plan of both somatic and stem cells. In particular, we focus on the biological relevance of bioelectricity in the pattern control that orchestrates both developmental and regenerative pathways. To this end, the narrative starts from the dawn of the first studies on animal electricity, reconsidering the pioneer work of Harold Saxton Burr in the light of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 116 publications
(106 reference statements)
1
3
0
Order By: Relevance
“…In addition, we also found with our ectopic transplantation paradigm that altering TNTP or ATP1A3 expression in delocalized DIN neurons prevented their axons to orient towards intact spinal cord tissue, as normally do the control conditions. This reveals that EFs can guide the axons over large scales, consistent with the view of EFs being vectors of both short and long-range topographic information and providing a spatial blueprint that orchestrates embryonic development 3337,49,92,97,99–101 . It also suggests that ATP1A3 has a cell-autonomous contribution to EF-mediated DIN axon navigation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, we also found with our ectopic transplantation paradigm that altering TNTP or ATP1A3 expression in delocalized DIN neurons prevented their axons to orient towards intact spinal cord tissue, as normally do the control conditions. This reveals that EFs can guide the axons over large scales, consistent with the view of EFs being vectors of both short and long-range topographic information and providing a spatial blueprint that orchestrates embryonic development 3337,49,92,97,99–101 . It also suggests that ATP1A3 has a cell-autonomous contribution to EF-mediated DIN axon navigation.…”
Section: Discussionsupporting
confidence: 79%
“…Next, we investigated how Na + /K + ATPases could control axons guidance. We postulated that they could be involved in a mechanism of guidance by electric fields (EF), based on literature reporting that Electric field (EF) provide positional information [33][34][35][36][37] during embryogenesis and that Na + /K + ATPases mediate EFdirected migration of cells 38 . Using a range of in vitro and in vivo approaches we found that ATP1A3 controls axon response to embryonic electric field (EF) generated by a transneuralepithelial potential.…”
Section: Introductionmentioning
confidence: 99%
“…When the DNA and all the components of the cell activate specific responses to biophotons and biophonons (which arrive with oscillations), the electrons of the double helices and the different cellular structures respond, creating oscillations of equal amplitude and rhythm, emitting new biophotons and phonons; these expand, creating new electromagnetic fields, both locally and distally [ 82 ]. The human body constantly receives and emits electromagnetic fields to maintain form and function [ 82 - 84 ]. The electromagnetic information travels as flows [ 85 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, the article named “Unveiling the Morphogenetic Code: A New Path at the Intersection of Physical Energies and Chemical Signaling” contributed by the Editor-in-Chief Carlo Ventura[ 1 ] motivated us to reconsider the biological roles of physical energies. In that article, the authors provided a detailed summary of the developmental history of physical energy, especially bioelectricity, as well as its applications and prospects in stem cell research.…”
Section: To the Editormentioning
confidence: 99%